Psychogenic Nonepileptic Seizures in Adolescence: Case Report - Cláudia Gomes Cano (Sociedade Portuguesa de Pediatria, 2021)
Psychogenic non-epileptic seizures are a functional neurological disorder characterized by time-limited disturbances of sensory-motor control accompanied by an alteration in consciousness, resembling epileptic seizures but with no ictal activity on electroencephalogram. Because psychogenic non-epileptic seizures mimic epileptic seizures, children and adolescents suffering from it are usually seen by neurologists.